Semantic components in Tuvan students’ perceptions of homeland - Seliverstova, Nina A.; Sorokin, Oleg V.; Oorzhak, Saylana U. (The New Research of Tuva, 2023)
The article is based on an analysis of Tuvan students’ ideas about the motherland and presents varieties of its meanings. We analyze perceptions of the homeland among Tuvan students using data received from focus groups (February and March 2022). Within the framework of the methodology of the holistic approach, Tuvan students are considered as part of the Tuvan society. At the same time, they represent the socio-demographic group “Russian youth”.The analysis has revealed the semantic structure of the studied group’s cultural space. In the cultural space of Tuvan students, there are traditional, modern and hybrid narratives of the motherland. This brings them closer to other Russian students.In the traditional accounts expressed by Tuvan students, there is a connection between the place of birth, the home of the ancestors and parents, love for this place and positive emotional reactions. In modern perceptions of the motherland, this connection is interrupted. There is a secularization of the attitude towards the homeland which has a sacred meaning in the traditional Tuvan culture. These narratives reflect the rationalization of the consciousness of Tuvan students, the priority of individual goals. This is a characteristic feature of Russian youth in general. The hybrid narratives of the motherland at the individual and group levels demonstrate a request for singularity and uniqueness of self-realization. They establish connections between (1) the right to choose a place of living and love for Tuva, recognition of Tuva as one’s homeland; (2) life on ancestral lands and the development of the motherland; (3) considering cases when compatriots call another country their homeland as a betrayal and implying that the homeland can betray as well, but in this case it is still felt to be one’s fatherland.The results of the analysis give a substantive and methodological basis for a quantitative study of the attitude of Tuvan young people to their motherland in relation to their civil and ethnic identities, perceptions about the future and attitudes to migration.
Keywords: Tuva; Tuvan youth; student youth; meaning of the motherland; Motherland; cultural space; self-regulation of life; Russian youth; patriotism